Calculating human capital: The market based valuation of the human resource - Roman Bechtel (Zeitschrift für Personalforschung (ZfP), 2007)
According to the Resource Based View of strategic management, analyzing the human resource of a specific firm in terms of its potential to serve as a source of a sustainable competitive advantage requires an examination of - among others - the resource value. The question of how to parameterize this value, i.e., how to calculate human capital, straightly leads to an integration of RBV reasoning with market based models of the competitive environment at the factor and product market side. However, there seems to be a tacit consent among strategy scholars that the only adequate market mechanism to be used for resource valuation is the product market with the economic rents effectively created there. Yet this regularly ends in a tautology criticism of the RBV. It thus is the particular purpose of this paper to examine what market mechanism really is the adequate one to use for the calculation of human capital. For this, a deductive methodology is used. In advancing the idea of a product market orientation, one encounters some major dilemmas ultimately leading to the conclusions that a product market based resource valuation is neither useful nor possible and that the resource value must be measurable independent from any product market success - thus invalidating the tautology criticisms at the same time. This is in direct and flagrant contradiction to the prevailing academic view. As a consequence of this, e.g., 'Value Added Approaches' and 'Return Based Approaches' of Human Capital Management are discredited as not conform to theoretical requirements and not useful for practical business management, whereas factor market based methods alone prove helpful.
Keywords: 330; human capital calculation; competitive advantage; resource based view (RBV); market based view (MBV); Humanvermögen; Wettbewerbsvorteil